Diga espelho meu, se há na avenida alguém mais feliz que eu!: estudo sobre identidade e memória da G. R. E. S. União da Ilha do Governador - Oliveira Neto, Paulo Cordeiro de (2008)
The carnival from Rio de Janeiro carries out a lot of meaningful elements which can be seen by those who admire and follow this big popular party, as well as for those who participe on it. the aim at this research is to propose the continuation of the analysing held at G.R.E.S. União da Ilha do Governador since 2003, during graduation in Social Sciences. The studying consists of verifying how the members see their collective identity within he Carnival universe and how a relation with the past and tradition is established, giving back symbols and some value that characterized them as a differentiated social group. the hypothesis is that the identity of this group is constituted basically by a collective memory activated by the samba enredo of a better acceptance, so much by their members named community, as the great public. this hypothesis raise a lot of enquires to be considered during the investigation and will take into consideration the use of these sambas by the school , in such a way that they are superdimensioned by the parades and how they are legitimed as identifiable elements of the guild, being so a way of collective representation. it is our belif that this research constitutes a good opportunity to know a bit better the social group considered and to discuss theoretically some fundamental categories within the anthropologic field